Four-Month Pregnancy Tradition: Internalization of Islamic Religious Education Values among Pregnant Women in Sripendowo Village, Lampung - Yulinda Yulinda; Dedi Setiawan; M. Saidun Anwar (CV. Bimbingan Belajar Assyfa, 2025)
This study aims to analyze the process of internalizing the values of Islamic Religious Education (PAI) among pregnant women through the four-month pregnancy tradition in Kampung Sripendowo, Lampung. The focus of the study includes three stages of internalization: acceptance, evaluation, and implementation of values. This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, involving religious leaders, traditional leaders, pregnant women, and community members as informants. Data analysis was conducted systematically through the stages of data reduction, data display, and conclusion drawing.The results of the study indicate that the four-month tradition functions as an effective non-formal educational medium. At the acceptance stage, religious values are conveyed through religious rituals such as Qur’an recitation, collective prayers, and advice from religious leaders. The evaluation stage is characterized by an affective process in which pregnant women assess the values based on Islamic teachings, psychological benefits, and social norms. The implementation stage shows real application in daily life, such as increased religious practices, improved moral behavior, and the practice of Islamic prenatal education.